2021
DOI: 10.1055/a-1528-1418
|View full text |Cite
|
Sign up to set email alerts
|

Conception and Feasibility of a Digital Tele-Guided Abdomen, Thorax, and Thyroid Gland Ultrasound Course for Medical Students (TELUS study)

Abstract: Purpose Medical education has been transformed during the COVID-19 pandemic, creating challenges regarding adequate training in ultrasound (US). Due to the discontinuation of traditional classroom teaching, the need to expand digital learning opportunities is undeniable. The aim of our study is to develop a tele-guided US course for undergraduate medical students and test the feasibility and efficacy of this digital US teaching method. Materials and Methods A tele-guided US course was established for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…USMed has been proven to be a feasible and well-accepted goal by medical students. In a recently published study, authors showed, that after only five hours of instruction, it has the ability to assist medical students gain basic competency in abdominal ultrasound examination ( 29 ). Many studies ( 30 32 ) have looked at the use of the Objective Structured Clinical Examination (OSCE), with Todsen et al ( 31 ) demonstrating strong reliability and evidence of construct validity of the OSAUS scale in an educational setting.…”
Section: Discussionmentioning
confidence: 99%
“…USMed has been proven to be a feasible and well-accepted goal by medical students. In a recently published study, authors showed, that after only five hours of instruction, it has the ability to assist medical students gain basic competency in abdominal ultrasound examination ( 29 ). Many studies ( 30 32 ) have looked at the use of the Objective Structured Clinical Examination (OSCE), with Todsen et al ( 31 ) demonstrating strong reliability and evidence of construct validity of the OSAUS scale in an educational setting.…”
Section: Discussionmentioning
confidence: 99%
“…Students created a digital portfolio stored on the ultrasound machine that was periodically reviewed during an in‐person meeting with a faculty member (Boulger et al, 2021 ). A tele‐ultrasound course was developed for undergraduate medical students in response to discontinued in‐person teaching (Höhne et al, 2021 ). Students received electronic resources for study before attending a live, videoconferencing lecture and demonstration of imaging technique.…”
Section: Discussionmentioning
confidence: 99%
“…Attention also needs to be given here to the visual design, which influences students' motivation to read the notes [53,54]. Alongside the use of analogue learning materials [28], there is also a clear trend toward increasing digitalization in ultrasound training [23,29,30,55,56]. The development and use of e-learning tools [24] should be intensified in the future so that echocardiographic skills can be taught using a "blended learning" approach [32,57] -a view that is also supported by some of the text comments provided in the evaluations.…”
Section: Minmentioning
confidence: 99%